Air Pollution Associated With Incident Stroke, Poststroke Cardiovascular Events, and Death: A Trajectory Analysis of a Prospective Cohort. (29th November 2022) - Tian, Fei; Cai, Miao; Li, Haitao; Qian, Zhengmin (Min); Chen, Lan; Zou, Hongtao; Zhang, Zilong; Wang, Chongjian; Xian, Hong; McMillin, Stephen Edward; Lin, Hualiang
Abstract : Background and Objective: Ambient air pollution has been widely linked with morbidity and mortality of stroke. However, its effects on dynamic progression trajectory of stroke remain unknown.We investigated the effects of ambient air pollution on progression trajectory from healthy status to incident stroke, poststroke cardiovascular diseases, and subsequent death. Methods: We retrieved 318, 752 participants from the UK Biobank. The annual concentrations of air pollution [particulate matter (PM2.5, PMcoarse, PM10 and PM2.5 absorbance), nitrogen dioxide (NO2 ), and nitrogen oxides (NOx )] were estimated through land use regressions. A multistate regression model was used to investigate the effects of air pollution on each stage of the progression of stroke. Results: During 3, 765, 630 person-years of follow-up, we identified 5, 967 incident stroke patients, 2, 985 poststroke cardiovascular patients, and 1, 020 deaths afterward. Each 5 μg/m 3 increase in PM2.5, NO2, and NOx was associated with the transition from healthy status to incident stroke [hazard ratios (HRs) (95% confidence intervals (CI)) = 1.24 (1.10, 1.40); 1.02 (1.00, 1.03); 1.01 (1.00, 1.02)] and transitions from healthy status to death directly [1.30 (1.21, 1.40); 1.03 (1.02, 1.04); and 1.02 (1.01, 1.02)]. We also observed positive associations for poststroke CVDs, especially for NO2 [1.04 (95% CI: 1.02, 1.06)], but these effects gradually declined for mortality outcome. Discussion: This study provides the first evidence that ambient air pollution is one important factor associated with the progression of stroke, and the effects differed across different clinical stages. A better understanding of the differential effects of air pollutants on different stroke transition stages could provide valuable insight toward targets for health management and clinical prevention.